The good, the bad, and the ugly ? controlling singlet oxygen through design of photosensitizers and delivery systems for photodynamic therapy. - Senge, Mathias (My University, 2018)
Singlet oxygen, although integral to photodynamic therapy, is notoriously uncontrollable, suffers from poor selectivity and has fast decomposition rates in biological media. Across the scientific community, there is a conscious effort to refine singlet oxygen interactions and initiate selective and controlled release to produce a consistent and reproducible therapeutic effect in target tissue. This perspective aims to provide an insight into the contemporary design principles behind photosensitizers and drug delivery systems that depend on a singlet oxygen response or controlled release. The discussion will be accompanied by in vitro and in vivo examples, in an attempt to highlight advancements in the field and future prospects for the more widespread application of photodynamic therapy.
PUBLISHED
Keywords: Photosensitizers; Singlet oxygen; Photodynamic therapy